Automatisierte kooperative Transition einer Regelungsaufgabe zwischen Mensch und Maschine am Beispiel des hochautomatisierten Fahrens - Ludwig, Julian (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2021)
This work proposes a concept based on haptic-shared control to assist humans in taking over a task from an automation, such as at the end of highly automated driving. The description of the interaction by time-variant differential games allows a model-based controller design as well as the estimation of the human's current readiness to take over. Several experiments demonstrate more performant and safe transitions with the new approach.